A Qualitative Evaluation of the Barriers and Facilitators Toward Implementation of the WHO Surgical Safety Checklist Across Hospitals in England. Issue 1 (January 2015) - Russ, Stephanie J.; Sevdalis, Nick; Moorthy, Krishna; Mayer, Erik K.; Rout, Shantanu; Caris, Jochem; Mansell, Jenny; Davies, Rachel; Vincent, Charles; Darzi, Ara
<x xml:space="preserve">Abstract</x> Objectives: To evaluate how the World Health Organization (WHO) surgical safety checklist was implemented across hospitals in England; to identify barriers and facilitators toward implementation; and to draw out lessons for implementing improvement initiatives in surgery/health care more generally. Background: The WHO checklist has been linked to improved surgical outcomes and teamwork, yet we know little about the factors affecting its successful uptake. Methods: A longitudinal interview study with operating room personnel was conducted across a representative sample of 10 hospitals in England between March 2010 and March 2011. Interviews were audio recorded over the phone. Interviewees were asked about their experience of how the checklist was introduced and the factors that hindered or aided this process. Transcripts were submitted to thematic analysis. Results: A total of 119 interviews were completed. Checklist implementation varied greatly between and within hospitals, ranging from preplanned/phased approaches to the checklist simply "appearing" in operating rooms, or staff feeling it had been imposed. Most barriers to implementation were specific to the checklist itself (eg, perceived design issues) but also included problematic integration into preexisting processes. The most common barrier was resistance from senior clinicians. The facilitators revealed some positive steps that can been taken to prevent/address these barriers, for example, modifying the checklist, providing education/training, feeding-back local data, fostering strong leadership (particularly at attending level), and instilling accountability. Conclusions: We identified common themes that have aided or hindered the introduction of the WHO checklist in England and have translated these into recommendations to guide the implementation of improvement initiatives in surgery and wider health care systems.